1992
DOI: 10.1007/bf01244735
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between glutamatergic and dopaminergic tone in the nucleus accumbens of mice: evidence for a dual glutamatergic function with respect to psychomotor control

Abstract: The rotation induced by a unilateral injection of the competitive NMDA receptor antagonist AP-5 was studied in mice with different tone in the central dopaminergic systems. AP-5 induced contralateral rotation in monoamine-depleted mice and in monoamine-depleted mice treated with a dopamine D-1 receptor agonist. In contrast, AP-5 induced predominantly ipsilateral rotation in monoamine-depleted mice treated with a mixed D-1/D-2 or a D-2 selective dopamine agonist and in mice with intact monoaminergic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 8 publications
1
14
0
1
Order By: Relevance
“…A unilateral injection of the competitive NMDA antagonist AP-5 caused the animals to rotate. The rotation was predominantly ipsilateral in monoaminergically intact animals, whereas the rotation in monoamine-depleted mice was exclusively contralateral (Svensson et al, 1992a). This shift in the direction of rotation was apparently due to lack of dopamine receptor stimulation, because in monoamine-depleted animals treated with the mixed dopamine agonist apomorphine, AP-5 caused the animals to rotate predominantly ipsilaterally (Svensson et al, unpublished findings).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A unilateral injection of the competitive NMDA antagonist AP-5 caused the animals to rotate. The rotation was predominantly ipsilateral in monoaminergically intact animals, whereas the rotation in monoamine-depleted mice was exclusively contralateral (Svensson et al, 1992a). This shift in the direction of rotation was apparently due to lack of dopamine receptor stimulation, because in monoamine-depleted animals treated with the mixed dopamine agonist apomorphine, AP-5 caused the animals to rotate predominantly ipsilaterally (Svensson et al, unpublished findings).…”
Section: Introductionmentioning
confidence: 89%
“…The D2 receptor agonist quinpirole reversed the contralateral rotation induced by AP-5 in monoamine-depleted animals into ipsilateral rotation. In contrast, in monoamine-depleted mice treated with the dopamine D1 receptor agonist SKF 38393, AP-5 still induced contralateral turning (Svensson et al, 1992a). These findings suggest that glutamate in the accumbens both can stimulate and inhibit motor functions, and that interactions with dopamine D2 receptors are crucial for the balance between glutamatergic stimulation and inhibition of behaviour.…”
Section: Introductionmentioning
confidence: 89%
“…In animals with intact monoaminergic systems, we have suggested that the balance between the two feedback circuits is shifted towards the positive feedback circuit, perhaps owing to the excitatory dopaminergic input to this circuit. Hence, in this case AP-5 will reduce the glutamatergic tone in the positive feedback circuit, rather than in the negative feedback circuit, and this should lead to a relatively higher activity in the positive feedback circuit on the untreated side, and accordingly ipsilateral rotation (Svensson, 1992b).…”
Section: Introductionmentioning
confidence: 98%
“…This shift in the direction of rotation was apparently due to lack of dopamine receptor stimulation, since AP-5 induced ipsilateral rotation in monoamine-depleted mice treated with the mixed dopamine agonist apomorphine (unpublished findings). These findings led us to suggest that glutamatergic neurotransmission in the nucleus accumbens has a dual function with regard to motor control (Svensson et al, 1992b).…”
Section: Introductionmentioning
confidence: 98%
“…[32][33][34][35][36] However, other studies have demonstrated that intrastriatal injection of the same NMDA receptor antagonists or NMDA receptors that mediate their effects through the same mechanism do not stimulate locomotor activity in animal models of Parkinson's disease. 33,34,[37][38][39][40] The reason behind these discrepancies may lie in the precise site of injection within the striatum and also the type of NMDA receptor antagonist administered. Similar disparities have arisen following systemic administration of NMDA receptor antagonists in animal models of Parkinson's disease.…”
mentioning
confidence: 99%